Chemoimmunotherapy: Coordination and Redox Dual‐Responsive Mesoporous Organosilica Nanoparticles Amplify Immunogenic Cell Death for Cancer Chemoimmunotherapy (Small 26/2021). Issue 26 (1st July 2021) - Zhang, Fan; Chen, Fangman; Yang, Chao; Wang, Lei; Hu, Hanze; Li, Xuezhao; Zheng, Xiao; Wang, Zheng; Chang, Zhimin; Li, Tianyu; Li, Li; Ge, Mingfeng; et al.
Abstract : In article number 2100006, Wen Sun, Wen‐fei Dong, Dan Shao, and co‐workers fabricate diselenide‐bridged mesoporous organosilica nanoparticles for coordination and redox dual‐responsive delivery of chemotherapeutic ruthenium compound KP1339. Such immunogenic cell death nano‐amplifier performed robust suppression on primary and distant tumor growth, as well as pulmonary metastasis of breast cancer with low systematic toxicity when combined with anti‐PD‐L1.